From Yalta to the Unknown: State Foreign Policy Features in the Transitional Period of the International Relations System - Kocharyan, Shavarsh (YSU Journal of International Affairs, 2025)
States face increased geopolitical volatility and uncertainty during transitional periods in the international relations system. Ensuring national security and strategically strengthening a country’s position internationally have emerged as the primary objectives of state foreign policy. States should be keen to form significant relationships with countries with similar long-term interests. Clear identification and consistent pursuit of national interests are crucial, as genuine partnerships can only develop when shared strategic priorities are recognized and effectively advanced. A state committed to its national interests naturally attracts authentic allies and accurately identifies its adversaries, whereas neglecting these interests leads to isolation and vulnerability. Within this context, a fundamental task of state foreign policy is the implementation of strategic initiatives that enhance a state’s global position without sacrificing core interests for the sake of external actors. As the international system moves towards an uncertain future, decisive interest-based foreign policy is essential for the states that aim to gain a stable and influential role in the new world order.
Keywords: international relations system; world politics; international legal system; foreign policy; national interest